The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00213-010-2031-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of MDMA (3,4-methylenedioxymethamphetamine) on EEG oscillations: alone and in combination with ethanol or THC (delta-9-tetrahydrocannabinol)

Abstract: RationaleTypical users of 3,4-methylenedioxymethamphetamine (MDMA or “ecstasy”) are polydrug users, combining MDMA with alcohol or cannabis [most active compound: delta-9-tetrahydrocannabinol (THC)].ObjectivesThe aim of the present study was to investigate whether co-administration of alcohol or THC with MDMA differentially affects ongoing electroencephalogram (EEG) oscillations compared to the administration of each drug alone.MethodsIn two separate experiments, 16 volunteers received four different drug cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
1
13
0
1
Order By: Relevance
“…Overall, effects of the pharmacological manipulation with moderate alcohol intoxication were weaker than the EOC effects, with alcohol increasing power in alpha and beta bands, especially under the eyes-closed condition. Our observation of alcohol-induced alpha increase is consistent with other evidence obtained with EEG (Kaplan, Hesselbrock, O’Connor, & DePalma, 1988; Lansbergen, Dumont, van Gerven, Buitelaar, & Verkes, 2011; Lukas, Mendelson, Kouri, Bolduc, & Amass, 1990). Furthermore, the increase in alpha power during alcohol challenge is higher in the offspring of alcoholics (Cohen, Porjesz, & Begleiter, 1993; Ehlers & Schuckit, 1991).…”
Section: Discussionsupporting
confidence: 93%
“…Overall, effects of the pharmacological manipulation with moderate alcohol intoxication were weaker than the EOC effects, with alcohol increasing power in alpha and beta bands, especially under the eyes-closed condition. Our observation of alcohol-induced alpha increase is consistent with other evidence obtained with EEG (Kaplan, Hesselbrock, O’Connor, & DePalma, 1988; Lansbergen, Dumont, van Gerven, Buitelaar, & Verkes, 2011; Lukas, Mendelson, Kouri, Bolduc, & Amass, 1990). Furthermore, the increase in alpha power during alcohol challenge is higher in the offspring of alcoholics (Cohen, Porjesz, & Begleiter, 1993; Ehlers & Schuckit, 1991).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, 5-HT is linked to the psychological effect of many psychotropic drugs; specifically, 5-HT 2A R activation has been reported to be essential for the psychological effects induced by various psychedelics ( Nichols, 2016 ), and in the case of MDMA, has been linked to perceptual and emotional alterations ( Liechti et al, 2000 ; Kuypers et al, 2018 ). Broadband reduction in oscillatory power, triggered by 5-HT 2A R, seems to be linked to the subjective effect of serotonergic drugs ( Carhart-Harris et al, 2016 ; Carhart-Harris and Friston, 2019 ) and has been consistently observed in humans and rodents following administration of MDMA ( Frei et al, 2001 ; Lansbergen et al, 2011 ) or various other 5-HT 2A R agonists ( Kometer et al, 2015 ; Muthukumaraswamy et al, 2013 ; Carhart-Harris et al, 2016 ; Wood et al, 2012 ). The link between 5-HT 2A R and perception is further supported by the fact that several routinely used antipsychotic drugs are potent 5-HT 2A R antagonists ( Marek et al, 2003 ; Meltzer, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Addictive substances have been found to alter brain electrical wave activities (Ceballos et al, 2009; Custodio et al, 2019; Lansbergen et al, 2011). Consistently, MAL and BOD, similar to METH, increased delta and gamma waves in mice.…”
Section: Discussionmentioning
confidence: 99%